Pengaruh Strategi Komunikasi Terhadap Kemampuan Keluarga Merawat Pasien Skizofrenia di Puskesmas Kedabu - Huda, Nurul; Ramadia, Arya; Fadhli, Rohmi; Ekaputri , Mersi (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: Family is very important to improve self-care abilities in people with schizophrenia, which includes support for the level of self-care abilities such as bathing, dressing, eating and defecating. The aim of this research is to analyze the influence of strategies for implementing self-care deficit communication on improving families in caring for schizophrenia patients at the UPT Puskesmas Kedabu Rapat. Methods: This article he research method used is quantitative with a Quasi Experimental research type. The research method used was one group pretest and posttest with control. Results: The results of the chi square statistical test on the experimental group showed a value of p=0.000<0.05, so H0 was rejected, which means there is no relationship between the influence of the strategy of implementing self-care deficit communication on improving families in caring for schizophrenic patients at the UPT Puskesmas Kedabu Rapat. Conclusion: The results of this study show that the higher the family support, the level of self-care ability for schizophrenia patients also increases. It is hoped that families can provide good family support to improve the self-care abilities of people with schizophrenia